Frequencies of Allo-antibodies In Pregnant Women - Abdelrahman, Mona; Bolad, Ahmed; Gader, Abdelgalil Abdel; Naema, M.; Yasmin, N.; Abdelwahab, A.; Algahtani, Farjah Hassan; Essam, A. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Hemolytic disease of the fetus and newborn (HDN) is a condition in which the lifespan of an infant’s red blood cells (RBCs) is shortened by the action of specific IgG antibodies directed against Rhesus or other blood group antigens on fetal RBCs that are inherited from the father but are not expressed by the mother. The aim of the present study was to provide data on the type and frequency of maternal RBC alloimmunization in pregnant women attending the ante-natal Clinics, King Khalid University Hospital between January 2010 to December 2010